Juniperus turbinata Guss. (Cupressaceae), novedad para la flora de Extremadura (España) - Vicente Orellana, José Alfredo; Galán de Mera, Antonio (Acta Botanica Malacitana, 2019)
Juniperus turbinata Guss. (Cupressaceae), a new record for the flora of in Extremadura (Spain) Palabras clave. Extremadura, Juniperus turbinata, Península Ibérica, sabinares. Key words. Extremadura, Juniperus turbinata, Iberian Peninsula, juniper schrublands.